Validasi Media Pembelajaran Biologi Menggunakan Adobe Animate pada Materi Keanekaragaman Hayati untuk Siswa SMA - Tri Ayu Lestari; Baiq Sri Handayani; Eni Suyantri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The concept of learning is currently trying to realize learning by utilizing technology to suit the times and the era of globalization. This development aims to make it easier for students to understand the concept of the digestive system interactively and efficiently in android-based learning media. This research method uses descriptive evaluative with a quantitative approach. The validation results from media experts, material validation, and product users were calculated and analyzed using quantitative data analysis techniques, and it was concluded that Android-based interactive media developed from Adobe Animate 2022 is suitable for use as a learning medium. This research succeeded in producing interactive multimedia products in biology subjects. The positive response results of students in the limited class trial obtained a score of 3.5 from a maximum score of 4 scores, this indicates that the application developed is feasible to be implemented in learning.